Finding stability in a time of prolonged crisis: Unconventional policy rules for Japan - McNelis, Paul D.; Yoshino, Naoyuki (Journal of Financial Stability, 2016)
This paper develops and estimates a dynamic stochastic general equilibrium (DSGE) model representing several key characteristics of Japan, namely, a large open economy, with large fiscal deficits and increasing amounts of debt held by domestic residents, through recurring sets of adverse shocks to productivity and positive shocks to government spending. We compare optimal simple rules for consumption tax rates, a Taylor rule with negative interest rates, and a quantitative easing rule, for reducing government debt held by the banking system, as well as optimizing welfare. In times of crisis, we show that the QE policy rule outperforms optimally-derived simple tax-rate rules or Taylor rules with negative interest rates for mitigating the costs of post-crisis adjustment and debt overhang.